THE EVOLUTION OF RADIOLOGICAL IMAGES IN A 4-MONTH-OLD INFANT WITH CONGENITAL PULMONARY AIRWAY MALFORMATION: A CASE REPORT - Sigiro, Rahel Margareth Febriana; Dini Rachma Erawati (International Journal of Radiology and Imaging, 2023)
Congenital pulmonary airway malformation, formerly known as congenital cystic adenomatoid malformation, is a heterogeneous group of cystic and non-cystic pulmonary lesions marked with the overgrowth of primary bronchioles, which is associated with an abnormal bronchial tree that does not have cartilage. A 4-month-old boy came with a complaint of productive coughs since he was 3 weeks old, fever since the age of 2 months, and shortness of breath. The patient was once hospitalized due to pneumonia and suspected tuberculosis. After undergoing serial chest radiographs, the results showed multiple cysts that were dominant in the lower lobe of both lungs with surrounding infiltrates. Through the confirmation of a chest CT scan, there were small, multiple cysts with a size of <2 cm in both lungs, connected to the bronchial branch, accompanied by consolidation with an air bronchogram suggestive of type 2 congenital pulmonary airway malformation. Congenital pulmonary airway malformation is a rare case that usually requires serial chest radiographs to assist in the establishment of its diagnosis and a CT scan for a definitive diagnosis of its lesions. Keywords: CPAM, congenital, pulmonary malformation, imaging